The Addition of Coconut Coir on Planting Medium and Watering Frequency Against The Growth of Oil Palm Sprouts (Elaeis quineensis Jacq.) in Pre Nursery - FINE FATE SIAHAAN; CHARLOQ CHARLOQ; FERRY EZRA T SITEPU (Jurnal Agroekoteknologi, 2018)
Pre nursery of oil palm requires adequate water availability on the media used so that with the addition of coconut coir helps keep soil moisture. The aims of the research is to know the addition of coconut coir on planting medium and watering frequency against the growth of oil palm sprouts in pre nursery. Research conducted in October through December 2016 in Pusat Penelitian Kelapa Sawit Sei-Aek Pancur, Tanjung Morawa, Deli Serdang. Research design used was Randomized Complete Design Factorial with two factors. The first factor is the addition consists of 1/5 coconut coir and 1/10 coconut coir, the second factor is the frequency of watering treatment consists of once and twice watering. The observation parameters is the plant height, number of leaves and stem diameter. The results showed that treatment of the addition of the coconut coir and the frequency of watering effect is not significant in the oil palm seedling growth. Keywords: Coconut coir, growth of oil palm sprout, watering frequency.